Analisis Sektor Basis di Kota Mataram Tahun 2010-2022 - Tri Intan Nuraeni; Debby Nindya Istiandari (FEB Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to analyze the potential sectors in Mataram City and the role of the government in increasing the competitiveness of these sectors to support economic growth. The research uses a quantitative descriptive approach with secondary data from the GRDP of Mataram Province and City. The analysis methods used include Location Quotient (LQ) to determine the leading sector and Shift-shareAnalysis to identify the level of economic growth. The results of the average LQ analysis for 2010-2022 show that the basic sectors in Mataram City include: (1) Manufacturing Industry; (2) Electricity and Gas Procurement; (3) Water Procurement, Waste Management, Waste, and Recycling; (4) Construction; (5) Wholesale and Retail Trade, Car and Motorcycle Repair; (6) Transportation and Warehousing; (7) Information and Communication; (8) Financial and Insurance Services; (9) Real Estate; (10) Corporate Services; (11) Government Administration, Defense, and Compulsory Social Security; (12) Educational Services; (13) Health Services and Social Activities; and (14) Other Services. The *Shift-share* analysis shows that the Wholesale and Retail Trade, Car and Motorcycle Repair sector has the highest competitiveness and a large contribution to the GRDP of Mataram City. This study recommends the government of Mataram City to prioritize the development of highly competitive base sectors to encourage sustainable economic growth.